Psychometric characteristics of an adapted measure of innovative behavior at work - Veloso, Ana (2021)
Purpose – The objective of this study is to test the psychometric properties of a self-reported measure of innovative behavior in the workplace, the Innovative Work Behavior (IWB) questionnaire, in Portuguese.  Design/methodology/approach – Two studies were carried out (one longitudinal and the other cross-sectional), based on the application of the questionnaire at two moments with an interval of 6 months in between (study I and study II). A longitudinal study was chosen, that is, the data were collected at two different moments, to reduce the most common biases. The Statistical Package for the Social Sciences (SPSS, ver. 26.0) and Analysis of Moment Structures (SPSS AMOS, ver. 22.0) were used.   Findings – The results of the two studies converge to a robust factor solution with one factor. The overall fit indices recorded for the model are quite robust, proving their quality in adjusting to the empirical data (2/ degrees of freedom = 32.8; CFI = 0.966 GFI = 0.970).  Originality/value – The IWB questionnaire is a fast, useful, and efficient measure to gauge innovative potential in the workforce, so its practical advantages are relevant and important. On a practical level, it is important to emphasize that evaluating the innovative behavior of employees can give important clues about the capacity of the organization/employer to foster innovation.